BAKU KELE: SOCIAL CAPITAL AND DISASTER MITIGATION FOR NOMADS STUDENTS OF THE COVID-19 PANDEMIC CRISIS IN AMBON CITY - Anwar, Ahsani Amalia (IAIN Ambon, 2021)
This study refers to how the Baku Kele culture can function as a form of social capital and disaster mitigation among students when facing difficulties during the Covid 19 pandemic crisis. The research method used is descriptive qualitative with a case study approach. The informants in this study amounted to 18 people who were nomads students from several campuses, both public and private in Ambon City. The data collection techniques used in this study were observations and interviews (indept interviews) which were conducted for 1 month from July 8-July 31, 2021. The results showed that the meaning of Baku Kele for nomads students in Ambon City refers more to difficult conditions or life crises experienced together, giving rise to feelings of empathy and compassion among nomads students to share, support each other (hand in hand) to go through life crises together and prioritize common interests over interests personal. The application of social values contained in the Baku Kele culture in the form of togetherness and unity values, sincerity values, and brotherhood values. The efforts to mitigate the spread of Covid 19 are carried out by students by jointly cleaning the environment around their homes and boarding houses, especially if they are on vacation. Along with technological advances digital technology that is very much attracting the attention of today's young generation could be that the Baku Kele cultural wisdom began to be eroded and no longer practiced so that over time it would disappear with the disappearance of social sensitivity in the community. For this reason, parents, educational institutions, and community leaders should continue to internalize the values of local cultural education to the generations of our nation so that they grow into individuals of character and noble character. Keywords: Baku Kele; Social Capital; Nomads Students; Covid 19 Disaster Mitigation.